A short perspective on the long road to effective treatments for Alzheimer's disease - Reynolds, David S. (British journal of pharmacology, 2019)
Globally, there are approximately 47 million people living with dementia, and about two thirds of those have Alzheimer's disease (AD). Age is the single biggest risk factor for the vast majority of sporadic AD cases, and because the world's population is aging, the number of people living with AD is set to rise dramatically over the coming decades. There are currently no disease‐modifying treatments for AD, and the few symptomatic agents available have limited impact on the disease. Perhaps surprisingly, there is relatively little activity in the AD research and development field compared with other diseases with a high mortality burden, such as cancer. There is enormous economic incentive to discover and develop the first disease‐modifying treatment, but previous failure has significantly reduced further industrial investment in this field. The short review looks at the historical path trodden to develop treatments and reflects on the journey down the road to truly effective treatments for people living with AD. Linked Articles This article is part of a themed section on Therapeutics for Dementia and Alzheimer's Disease: New Directions for Precision Medicine. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v176.18/issuetoc